Parameatal cyst: A report of five cases - Pankaj Halder; Kartik Chandra Mandal; Rajarshi Kumar; Madhumita Mukhopadhyay (Wolters Kluwer Medknow Publications, 2017)
The parameatal cyst (PMC) is a rare and benign lesion which occurs in newborn, children, or even in adults. We present five patients of PMC to discuss its embryology, clinical presentation, and the treatment along with a brief review of literature.